Assessing the quality, reliability and readability of online health information regarding systemic lupus erythematosus. (October 2018) - Reynolds, M; Hoi, A; Buchanan, R R C
Introduction: Systemic lupus erythematosus (SLE) has complex pathophysiology and treatments, and patients often use the internet to better understand their condition. This report systematically assesses the quality, reliability and readability of online information. Methods: The search term 'systemic lupus erythematosus' was used with Google™, Bing™ and Yahoo™ search engines sequentially. The first 25 websites returned ('hits') for each search engine (total 75 websites) were compiled. The search terms 'SLE' and 'lupus' were used in separate Google searches to assess for commonality. After removal of excluded hits, websites were assessed using the DISCERN instrument, Journal of the American Medical Association benchmarks and Gunning Fog Index for quality, reliability and readability and presence of 'Health on the Net Code' (HoN) standardisation recorded. Results: There was a large degree of commonality among hits from the three different search engines using the search term 'systemic lupus erythematosus', as well as hits returned for the three different search terms using Google. The mean DISCERN score was 47.7 (SD 13.2) for 'systemic lupus erythematosus', 46.4 (SD 14.2) for 'SLE' and 45.2 (SD 10.1) for 'lupus', with no statistically significant difference. The mean number of JAMA benchmarks (maximum four) present for the 'systemic lupus erythematosus', 'SLE' and 'lupus' searches was 1.3 (SD 1.2), 1.4 (SD 1.3) and 1.2 (SD 1.0), respectively, with no statistically significance difference. The average readability of hits for the three different search terms was 9.3 (SD 3.4), 10.0 (SD 3.1) and 11.1 (SD 2.7), with no statistically significant difference. Conclusion: There was a large degree of commonality of hits among the different search engines and the utilised search terms but they are not synonymous. Regardless of search term, the overall quality of websites was fair, whilst reliability was poor. Websites appearing higher in searches did not score better. Presence of the HoN did not represent better quality. Readability was higher than recommended for near-universal understanding. There was no difference in quality, reliability or readability of websites using the search terms 'systemic lupus erythematosus', 'SLE' or 'lupus', with some high-scoring websites appearing in only one search term result. This study reminds clinicians to direct patients to high-quality websites rather than rely on search engines.